PYCR1 knockdown inhibits the proliferation, migration, and invasion by affecting JAK/STAT signaling pathway in lung adenocarcinoma. Issue 5 (4th March 2020) - Gao, Yawen; Luo, Lihua; Xie, Yangchun; Zhao, Yu; Yao, Jie; Liu, Xianling
Abstract: Lung adenocarcinoma (LUAD), as a form of non‐small cell lung cancer (NSCLC), is the most frequently diagnosed lung cancer worldwide. To date, a few biomarkers have been reported to provide valuable information in guiding LUAD treatment. The aim of our study was to explore the functional role of pyrroline‐5‐carboxylate reductase 1 (PYCR1) in LUAD. Based on Oncomine database, we found that PYCR1 was highly expressed in LUAD tissues. We also confirmed an abnormal increase of PYCR1 expression in LUAD cell lines and patients' tissues. Through Kaplan‐Meier plotter database, we further studied the prognostic values of PYCR1. The outcomes indicated that overexpressed PYCR1 associated with poor prognosis among LUAD patients. To further study the function of PYCR1 in LUAD, cell counting kit‐8, colony‐forming, scratch wound healing, and Transwell assays were conducted. The results suggested that knockdown of PYCR1 curbed cell proliferation, migration, and invasion in LUAD cell lines. Subsequently, we identified 50 top genes positively and negatively correlated with PYCR1 in LUAD, and conducted biological pathway enrichment analysis of these genes. Among those enriched pathways, we selected JAK/STAT signaling pathway for further analysis. The results of Western blot assays revealed that PYCR1 knockdown significantly increased the expression of Bcl‐2 and c‐Myc, and the phosphorylation level of JAK2 and STAT3. Taken together, this study unearthed that PYCR1 knockdown could inhibit tumor growth and affect the JAK/STAT signaling pathway in LUAD. This study may contribute to a better understanding of PYCR1 in LUAD and provide a potential biomarker for cancer prognosis.